Child sexual exploitation : why theory matters / edited by Jenny Pearce ; with a foreword by Julia Davidson. - Pearce, Jenny J. (Policy Press, 2019)
The issue of Child Sexual Exploitation (CSE) is firmly in the public spotlight internationally and in the UK, but just how well is it understood? To date, many CSE-related services have been developed in reaction to high profile cases rather than being designed more strategically. This much-needed book breaks new ground by considering how psychosocial, feminist and geo-environmental theories, amongst others, can improve practice understanding and interventions. Edited by one of the leading scholars in the field, this is an essential text for students and those planning strategic interventions and practice activities in social, youth and therapeutic work with young people, as it supports understanding of how CSE arises and how to challenge the nature of the abuse.